Genetic Diversity of MHC B-F/B-L Region in 21 Chicken Populations - Yuan, Yiming; Zhang, Huanmin; Yi, Guoqiang; You, Zhen; Zhao, Chunfang; Yuan, Haixu; Wang, Kejun; Li, Junying; Yang, Ning; Lian, Ling (Frontiers in Genetics, 2021)
The chicken major histocompatibility complex (MHC) on chromosome 16 is the most polymorphic region across the whole genome, and also an ideal model for genetic diversity investigation. The MHC B-F/B-L region is 92 kb in length with high GC content consisting of 18 genes and one pseudogene (Blec4), which plays important roles in immune response. To evaluate polymorphism of the Chinese indigenous chickens as well as to analyze the effect of selection to genetic diversity, we used WaferGen platform to identify sequence variants of the B-F/B-L region in 21 chicken populations, including the Red Jungle Fowl (RJF), Cornish (CS), White Leghorns (WLs), 16 Chinese domestic breeds, and two well-known inbred lines 63 and 72. A total of 3,319 single nucleotide polymorphism (SNPs) and 181 INDELs in the B-F/B-L region were identified among 21 populations, of which 2,057 SNPs (62%) and 159 INDELs (88%) were novel. Most of the variants were within the intron and the flanking regions. The average variation density was 36 SNPs and 2 INDELs per kb, indicating dramatical high diversity of this region. Furthermore, BF2 was identified as the hypervariable genes with 67 SNPs per kb. Chinese domestic populations showed higher diversity than the WLs and CS. The indigenous breeds, Nandan Yao (NY), Xishuangbanna Game (XG), Gushi (GS), and Xiayan (XY) chickens, were the top four with the highest density of SNPs and INDELs. The highly inbred lines 63 and 72 have the lowest diversity, which might be resulted from a long-term intense selection for decades. Collectively, we refined the genetic map of chicken MHC B-F/B-L region, and illustrated genetic diversity of 21 chicken populations. Abundant genetic variants were identified, which not only strikingly expanded the current Ensembl SNP database, but also provided comprehensive data for researchers to further investigate association between variants in MHC and immune traits.